Biomarcadores de estresse oxidativo e dos hormônios pancreáticos: estudo in vivo do pâncreas endócrino de descendentes de ratas diabéticas submetidos ou não à dieta hiperlipídica - Souza, Franciane Quintanilha Gallego (Universidade Estadual Paulista (Unesp), 2025)
During intrauterine life, changes occur that can influence embryofetal development and the adult life of offspring, increasing the risk of disease. An unfavorable intrauterine environment, combined with current lifestyles—such as high energy consumption, minimal physical activity, stress, and anxiety—are some of the many factors implicated in the development of diabetes, obesity, and other metabolic disorders. Considering the current human situation regarding offspring of diabetic mothers exposed to an inadequate (high-calorie) diet in postnatal life, we intend to evaluate how the combination of these two unfavorable conditions (inadequate intrauterine environment and consumption of a high-fat diet after weaning) will affect the distribution of pancreatic endocrine cells and markers of oxidative stress in these cells in offspring of diabetic rats in adulthood. Furthermore, we intend to standardize the technique for isolating pancreatic islets in rats, which will be used in various projects in our laboratory and in other graduate programs. Therefore, the objective of this study is to evaluate biomarkers related to oxidative stress and pancreatic endocrine hormones in an in vivo study of adult offspring of diabetic rats fed a high-fat diet after weaning. This project is divided into three subprojects: Subproject 1 – Standardization of the pancreatic islet isolation technique in rats of different ages; Subproject 2 – an in vivo experiment using daughters of diabetic Sprague Dawley rats, exposed or not to a high-fat diet from weaning to adulthood. Four experimental groups were constituted (n = 10 animals/group): 1. offspring of non-diabetic mothers (control) exposed to a standard diet (commercial chow - DP), 2. offspring of non-diabetic mothers (control) exposed to a high-fat diet (HFD - diet prepared with 40% more lipids in reaction to the commercial chow), 3. offspring of diabetic mothers exposed to DP, 4. offspring of diabetic mothers exposed to HFD. At four months of age (adult life), all rats underwent the oral glucose tolerance test (OGTT) and, one week after this test, the rats were anesthetized and killed for blood collection for measurement of insulin, antioxidant enzymes and cell death by apoptosis. To evaluate the transgenerational effect of maternal diabetes, we intend to evaluate all the parameters mentioned in Subproject 2 in granddaughters of diabetic rats in an in vivo experiment as well – Subproject 3. For all statistical comparisons, a minimum confidence limit of 95% (p<0.05) was considered.
Biomarcadores de estrés oxidativo y hormonas pancreáticas: estudio in vivo del páncreas endocrino de crías de ratas diabéticas sometidas o no a una dieta rica en grasas
Keywords: Diabete; Dieta hiperlipídica; Ilhotas pancreáticas; Estresse oxidativo; Ambiente intrauterino inadequado; Ratas